The Female Body in the Arab Muslim World: Historical and Sociological Analysis - Akrachi, Nadir (Integrated Journal for Research in Arts and Humanities, 2024)
The purpose of this paper is to historically and sociologically analyze the image and perception of the female body in the Arab Muslim world. It explores how such views have metamorphosed over time, starting from the pre-Islamic era to today’s global society, as a result of cultural, religious and socio-political factors. The research uncovers female identity and dynamics of its expression and is devoted to the analysis of literary, artistic and religious sources aimed at showing how tradition and modernity coexist. It also discusses the impact feminist movements and globalization have had on regional women’s experiences and norms. Focusing on the prevailing problems and changes that women face in the world today, this detailed research intends to contribute to the broader debate on the issues of gender, culture and identity in the Arab Muslim context.